Semi-Automated Methods For Femur Length Measurements In Fetal Ultrasound Images - Rahmatullah, Bahbibi (2007)
Measurement of fetal femur length is crucial for the estimation of fetal age and growth pattern. An automatic system for femur recognition and measurement in ultrasound images could promote the standardisation of fetal femur measurements and resulting in a more reliable age estimates.